Association of weight-adjusted-waist index with asthma prevalence and the age of first asthma onset in United States adults - Yu, Longshan; Chen, Yan; Xu, Ming; Li, Rongfu; Zhang, Juan; Zhu, Shouwei; He, Zongbao; Chen, Mingwei; Wang, Gaosheng (Frontiers in Endocrinology, 2023)
Objective:Aim of this study was to assess whether the WWI (weight-adjusted-waist)index is associated with the prevalence of asthma and age when first asthma onset appear in US adults. Methods:To assess the relationship between the WWI index and the incidence of asthma and age at onset of asthma,we selected participants from the National Health and Nutrition Examination Survey(NHANES)database between 2001 and 2018.A dose-response curve was calculated using logistic regression,subgroup analysis,and a dose-response curve. Results:The study included 44480 people over the age of 20,of whom 6061 reported asthma,and the increase in asthma incidence was 15%associated with each unit increase in the WWI index,after adjusting for all confounders(OR=1.15,95%CI:1.11,1.20).The sensitivity analysis was also performed by trichotomizing the WWI,and compared to the lowest tertile,the highest tertile WWI group displayed a 29%increase in asthma incidence(OR=1.29,95%CI:1.19,1.40)A nonlinear correlation was found between the WWI index and the risk of asthma onset, with a threshold saturation effect indicating an inflection point of 10.53 (log-likelihood ratio test, P<0.05), as well as a positive linear correlation with age at first asthma onset. Conclusions:Despite the lack of a causal relationship between higher WWI index and asthma incidence and age of onset,there is still a positive association between WWI index with these two factors that deserves clinical attention.